2022
DOI: 10.1109/tpami.2020.3009758
|View full text |Cite
|
Sign up to set email alerts
|

Tasks Integrated Networks: Joint Detection and Retrieval for Image Search

Abstract: The traditional object (person) retrieval (re-identification) task aims to learn a discriminative feature representation with intra-similarity and inter-dissimilarity, which supposes that the objects in an image are manually or automatically pre-cropped exactly. However, in many real-world searching scenarios (e.g., video surveillance), the objects (e.g., persons, vehicles, etc.) are seldom accurately detected or annotated. Therefore, object-level retrieval becomes intractable without bounding-box annotation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 63 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Second, the difference between different media semantics lies not only in their corresponding feature values, but also in the characteristics used to define them; The methods of using these features in media content analysis may also be different. This makes it difficult to classify various media semantics accurately and reliably [9]. There are two basic ideas to solve this problem.…”
Section: Methodology Of Multimedia Fusion Analysismentioning
confidence: 99%
“…Second, the difference between different media semantics lies not only in their corresponding feature values, but also in the characteristics used to define them; The methods of using these features in media content analysis may also be different. This makes it difficult to classify various media semantics accurately and reliably [9]. There are two basic ideas to solve this problem.…”
Section: Methodology Of Multimedia Fusion Analysismentioning
confidence: 99%
“…4. The results of two-step methods (Chang et al 2018;Chen et al 2018;Lan, Zhu, and Gong 2018;Han et al 2019;Wang et al 2020) are shown in the upper block while the one-step methods (Xiao et al 2017(Xiao et al , 2019Liu et al 2017;Yan et al 2019;Zhang et al 2020;Munjal et al 2019;Chen et al 2020) To evaluate the performance consistency, we also compare with other competitive methods under varying gallery sizes of [50,100,500,1000,2000,4000]. Fig.…”
Section: Comparisons With the State-of-the-art Methodsmentioning
confidence: 99%
“…4. The results of two-step methods (Chang et al 2018;Chen et al 2018;Lan, Zhu, and Gong 2018;Han et al 2019;Wang et al 2020) are shown in the upper block while the one-step methods (Xiao et al 2017(Xiao et al , 2019Liu et al 2017;Yan et al 2019;Zhang et al 2020;Munjal et al 2019;Chen et al 2020) in the lower block. To evaluate the performance consistency, we also compare with other competitive methods under varying gallery sizes of [50,100,500,1000,2000,4000].…”
Section: Ablation Studymentioning
confidence: 99%